1952
DOI: 10.1002/hlca.19520350740
|View full text |Cite
|
Sign up to set email alerts
|

Spektrophotometrische Untersuchung saurer Chloritlösungen

Abstract: The spectrophotometric method is shown to be very effective in the examination of acid chlorite solutions, inasmuch as among the ionic and molecular species which come into consideration – ClO2, ClO2′, HClO2, ClO3′ and Cl′ – the first three demonstrate characteristic absorption spectra which are suitable to detect and quantitatively determine these compounds. The log ε‐curves for ClO2, ClO2′, HClO2 and ClO3′ are communicated in the wave lenght region of 2200–4800 Å. ClO2, ClO2′ and HClO2 can be simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

1958
1958
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 6 publications
1
6
0
2
Order By: Relevance
“…Avec [14], du fait de la prtpondtrance de [15] par rapport a [16], on prevoit une formation relative de CIOz beaucoup plus importante que celle obt'enue expCrimentalement pour la reaction catalyste par le fer. Nous admettons donc que, dans nos conditions, la rupture est [13]. Ce n'est pas necessairement vrai en milieux moins acides.…”
Section: Interpretation Des Resultatsunclassified
See 1 more Smart Citation
“…Avec [14], du fait de la prtpondtrance de [15] par rapport a [16], on prevoit une formation relative de CIOz beaucoup plus importante que celle obt'enue expCrimentalement pour la reaction catalyste par le fer. Nous admettons donc que, dans nos conditions, la rupture est [13]. Ce n'est pas necessairement vrai en milieux moins acides.…”
Section: Interpretation Des Resultatsunclassified
“…Lorsqu'on augmente le pH, la vitesse de dismutation du chlorite passe par un maximum vers pH = 2 (3,13 (14).…”
unclassified
“…[6] explains the contradictory observations published in the literature. When the concentration of sodium chlorite is in excess, the reaction between HC10, and C10,-will be predominant, and the reaction order with respect to H f will be close to 1, as observed by Stitt et al (5).…”
Section: ) Reaction Ordersmentioning
confidence: 92%
“…The reaction appeared to be nearer to first order with respect to the equilibrium concentration of hydrogen ions than second order, the numerical values falling between 1.0 and 1.2. Buser and Hanisch (6) found that the rate of formation of chlorine dioxide in dilute chlorite solution is not a simple function of pH. They observed a maximum reaction rate at DH 1.70 for a solution of 3.18 x M ~a~1 0 , .…”
mentioning
confidence: 98%
“…The EFFECTS OF C103 AND C102 ON NITRIFICATION 1179 determinations of NO2and N03were unaffected by 10 mM C103and were affected by C102only at >0.6 mM; in the latter case, appropriate corrections (<5% at 1.0 mM C102 ) were made. The concentration of C102 in ifitrates was determined by a method based on Cl02 UV absorbance at 260 nm (A260) (2). The minimum detection limit was about 50 ,uM C102 .…”
Section: Methodsmentioning
confidence: 99%